Controlled trial of respiratory muscle training in chronic airflow limitation. Issue 8 (August 1992) - Guyatt, G; Keller, J; Singer, J; Halcrow, S; Newhouse, M
Abstract : BACKGROUND: Whether respiratory muscle training is of benefit to patients with chronic airflow limitation is controversial. The objective of the study was to determine the effect of resistance breathing training on physiological and functional measures in patients with chronic airflow obstruction. METHODS: The design was a randomised, double blind, controlled trial with a six month follow up. Eighty two patients with a forced expiratory volume in one second (FEV1) of less than 70% predicted, and an FEV1/vital capacity ratio of less than 0.7, were randomised to receive training for 10 minutes five times daily with progressively larger resistances through a resistive breathing device (PFLEX) as tolerated or to a sham device which gave minimal resistance. The main outcome measures, respiratory muscle strength and endurance, a progressive exercise test, a six minute walk test and physical and emotional function (chronic respiratory questionnaire) were assessed at monthly intervals. Patients in both groups were also randomised to wear or not wear nose clips during their training. RESULTS: No significant differences were observed between treatment and control groups, with or without nose clips, for any of the outcomes. Confidence intervals on the difference between treatments were narrow, excluding clinically important difference in any major outcome. CONCLUSION: This training regimen fails to strengthen respiratory muscles or improve exercise or functional capacity in patients with chronic airflow limitation.